PENGARUH SERBUK CANGKANG TELUR AYAM DAN NPK GROWER TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT CERI (Solanum lycopersicum var. Cerasiforme - Mhd. Fahdi Afif; Sri Mulyani (DINAMIKA PERTANIAN, 2025)
The study entitled the Effect of Chicken Eggshell Powder and NPK Grower on the Growth and Production of Cherry Tomato Plants (Solanum lycopersicum var. cerasiforme) was conducted at the Experimental Farm of the Faculty of Agriculture, Riau Islamic University, Bukit Raya District, Pekanbaru City, for four months from October 2024 to January 2025. This study used a Factorial Completely Randomized Design consisting of two factors. The first factor was chicken eggshell powder, consisting of four treatment levels: 0, 157, 314, and 471 g per plot, while the second factor was NPK grower, consisting of four treatment levels: 0, 7.5, 15, and 22.5 g per plant. The parameters observed were plant height, flowering age, harvest age, number of productive branches, number of fruits per plant, fruit weight per plant, number of remaining fruits, and soil pH. The data were statistically analyzed and then subjected to the 5% BNJ test. The results showed that the interaction between chicken eggshell powder and NPK grower affected all observation parameters. The best treatment was 471 g chicken eggshell powder per plot and 22.5 g NPK grower per plant. The main factor of chicken eggshell powder affected all observation parameters. The best treatment was 471 g of chicken eggshell powder per plot. The main factor, NPK grower, affected all observation parameters. The best treatment was an NPK grower dose of 22.5 g per plant.